?ABUNDANCE, DISTRIBUTION AND DIVERSITY OF BACILLUS THURINGIENSIS IN PAKISTANIAN ENVIRONMENT (Biological Sciences - PJSIR, 1995)
Four hundred and seventy six samples of soil, insect cadavers, wild animal dung, decaying leaves and grain dust collected from different ecological environments in Pakistan, were used as source material to separate 647 Bacillus thuringiensis isolates. The abundance and frequency of Bt in the various samples was found to be in the order of soil> grain dust> wild animal dung> bird droppings> others. Isolates were randomly selected to study pesticidal protein profile on SDS-PAGE and entomocidal properties in biotoxicity assays against Heliothis armigera (Lepidoptera) and Anophelese stephensi (Diptera). Several isolates were more efficacious against Heliothis armigera than the available reference strain.